Severe AV Shunt-Related Sepsis in a Chronic Dialysis Patient With Immobility and Protein Energy Wasting: A Case Report and Literature Review - Putra, I Putu Eka Dharma (Siber Journal of Advanced Multidisciplinary, 2025)
Vascular access infections, particularly those involving arteriovenous (AV) shunts, are a major cause of morbidity and mortality in chronic hemodialysis patients, especially among those with prolonged access use, immunocompromise, and comorbidities such as malnutrition or immobility. Case Report: We describe a 62-year-old female with end-stage renal disease (ESRD) undergoing dual dialysis modalities (hemodialysis and CAPD), who developed sepsis secondary to an infected left brachial AV shunt. Her condition was further complicated by three years of immobilization due to untreated bilateral femoral fractures and severe protein-energy wasting (PEW). Discussion: This case illustrates the diagnostic and therapeutic challenges of sepsis in dialysis patients, including atypical clinical presentation, altered inflammatory markers, and the complexity of antibiotic management in the setting of renal failure. Furthermore, it underscores how overlapping clinical issues such as infection risk, poor nutritional status, and physical dependency necessitate an integrated approach to care. Conclusion: Early recognition of AV shunt infections and prompt intervention are critical to preventing systemic complications. Comprehensive multidisciplinary collaboration is essential for improving outcomes in ESRD patients with complex comorbidities, emphasizing infection control, nutritional rehabilitation, mobility support, and individualized dialysis planning.